JALUR KERETA API SEMARANG-SURAKARTA DAN PENGARUH SOSIAL EKONOMI DI KARESIDENAN SURAKARTA (1864-1930) - , Waskito Widi Wardojo, SS. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis discusses the railway route of Semarang- Solo and social change in Karesidenan Surakarta in 1864-1930. The central questions of this thesis are, how the social change was happened in the society of Karesidenan Surakarta as the result the built of train railway route Semarang- Surakarta (Vorstenlanden). The questions would be discussed throught the comprehensive study toward the process of the railway infrastructure development based on the related documents and manuscripts. The main source of data comes from archives, annual reports, journal and magazines. The conclusion of this research is that railway development of Semarang-Vorstenlanden route is along process which is backgrounded by colonial interest to exploit the tropical product. The distribution of export commodities from countryside to the sea port was faster due to the railway development. The colonial government was also richer and richer because of the railway existence. The train had played more role than just accelerated tropical product transportation, yet it also had supported the raise of social changing. This made the train became the new mode in the transportation which brings modernity value. The railway and the station had a significant role in exploring some new areas into reachable regions. It gave an impact in the increase of both economic condition of the urban people and the mobility of the citizen has created a âspoor kultuurâ, which includes an understanding of the time, recognition of currency, and more importantly the discrimination from the colonial government to the indigenous citizen.